THE EFFECT OF ANTAGONIST PLANTS IN SUPPLYING THE PROGRESS OF THE EVENT OF GANODERMA SP ROOT DISEASE - Oktora Matondang, Christina; Muklasin, Muklasin; Nurhayati, Nurhayati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Activity Testing the Effect of Antagonist Plants in Suppressing the Development of Incidence of Root Rot Disease Ganoderma sp. aims to determine the effect of antagonist plants in suppressing the development of stem rot disease incidence of Ganoderma sp. in oil palm nurseries. The study used a randomized block design with 7 treatments, namely Ganoderma+ginger isolate, Ganoderma+turmeric isolate, Ganoderma+lemongrass isolate, Ganoderma+temulawak isolate, Ganoderma+garut isolate, Ganoderma isolate and control. Each treatment with 5 replications with 2 sample plants. The parameters observed were the development of disease incidence through symptoms, height and number of leaf midribs of oil palm seedlings. The data were analyzed using the SPSS program. The effect of the treatment was analyzed by using fingerprints. If there is a treatment that has a significant effect, further tests are carried out with Duncan's Multiple Distance Test (DMRT) with a level of : 0.05. Based on the test results, it was found that the incidence of Ganoderma stem rot disease was the fastest, highest and most developed in each observation, namely in the treatment using ginger and lemongrass antagonists. While the lowest incidence of disease was found in the treatment of arrowroot, turmeric and temulawak. These antagonist plants have exudate containing antibiotics that can inhibit the growth of the Ganoderma fungus. The development of oil palm seedling plant height is strongly influenced by the physical properties of the soil and the presence of Ganoderma pathogens. While the Ganoderma pathogen did not affect the development of the number of leaf midribs, but only caused changes in leaf color such as necrosis.